Changes in precipitation extremes in Brazil (Paraná River Basin) - Zandonadi, Leandro [UNESP]; Acquaotta, Fiorella; Fratianni, Simona; Zavattini, João Afonso [UNESP] (Springer Nature, 2016)
This research was aimed at addressing aspects related to variation in the amount of precipitation during the period from 1986 to 2011 in the Paraná River Hydrographical Basin, Brazil, for 32 meteorological stations using 11 climate indices created by the ETCCDI (Expert Team, ET, on Climate Change Detection and Indices, ETCCDI). The daily rainfall data were organized in spreadsheets, which were subjected to an intense quality control and an accurate historical research. For each pluviometric index, we have estimated the trends and the statistical significant of the slopes have been calculated. The results confirm that an increase in total precipitation in almost all analyzed stations was registered, and the extreme precipitations were the main contributors to such additions. In fact, the significant increase in total annual rainfall in north-central sector of the basin are related to higher rates of heavy rain, mainly above 95th percentile, as well as to the highest event of rainfall above 10 mm. Instead the northern part of the region, showed declining trends of extreme rainfall, caused mainly by the reduction in the rainfall occurrences over 95th percentile. In order to evaluate the impact that the increasing extreme rainfall may cause in large urban centers, we have investigated the data of two municipalities (Curitiba, PR and Goiânia, GO-Brazil), where the positive trend can cause inconvenience to the population (floods and inundations) suggesting, at least, the need of implementation of more effective urban planning for the future.